Online Marketing Optimization To Increase Anggun Hijab Profit: (Case Study Of MSME’s Anggun.Hijab) - Ima Wahyu Dewi Saputri; Retno Wijayanti; Nanik Kustiningsih; Iwang Suwangsih (LPPPIPublishing, 2022)
Anggun.hijab is one of the many MSME’s in the field of Muslim clothing in Indonesia. The products produced are various hijabs that suit the needs of Muslim women. With a diverse target market, both children, teenagers, and adults. However, in the current era of the covid-19 pandemic, Anggun.hijab is more focused on selling and marketing with an online system, to reduce the impact of the spread of covid-19. The purpose of this study is to describe the importance of digital marketing to optimize the increase in profit for MSME’s Anggun.hijab. And also because there are many competitors in the same field, entrepreneurs must create innovations that can attract consumers. This study uses a descriptive qualitative method of collecting data by means of direct interviews with the team from Anggun.hijab. The problem to be researched is the optimization of online marketing to increase profits for Anggun.hijab MSME’s. The results of this study are known that digital marketing techniques can increase sales volume which will have an impact on increasing profits. With the implementation of digital marketing, there was a significant increase in sales, from 20 pcs in the first week to 44 pcs in the second week.